Prevalence of Tuberculosis in Patients with Liver Cirrhosis - Sharma, Dilip; KC, Sudhamshu; Jaisi, Bikash (Journal of Nepal Health Research Council, 2018)
Background: Studies have shown that patients with liver cirrhosis are more susceptible to tuberculosis because of immune dysfunction; however there are only limited data. We carried out this study to know the prevalence and clinical characteristics of tuberculosis in patients with liver cirrhosis. Methods: In this retrospective study, medical files of 200 consecutive patients admitted with diagnosis of liver cirrhosis in the medical ward of liver unit, Bir Hospital from January 2011 to December 2014 were evaluated for the presence of TB and clinical characteristics of these patients were analyzed. Results: Eighteen patients were diagnosed to have tuberculosis with a prevalence of 9%. The median age of patients with tuberculosis and liver cirrhosis was 53 (35–71) years and M: F ratio was 2:1. 67%, P=0.01). Median CTP score of patients were 8.5 (5–12) (CTP A: B: C: 3:7:8). Extra pulmonary tuberculosis was more common (67%) than pulmonary (33%). In extra pulmonary tuberculosis, distribution was as pleural effusion (n=4), abdominal (n=4), intestinal (n=2), peritoneal (n=9), and pott’s spine (n=2). Conclusions: Tuberculosis is prevalent in patients with liver cirrhosis. Extra pulmonary tuberculosis was more compared to pulmonary tuberculosis. Tuberculosis was common in decompensated liver cirrhosis than compensated liver cirrhosis .